Modernizing National Numbering Plan on NGN Platform - Hungarian Case Study - G. Sallai; I. Abos; G Adamis; P. Sziráki; E. Tamási (International Telecommunications Society (ITS), 2010)
The intensive technological development of the last years brought the overall acceptance of an IP based network and services vision based on the NGN. The realization of the NGN vision, the decision on the migration to NGN sets regulatory tasks, especially in the area of numbering and addressing. The utilization of the opportunities provided by the NGN platform requires the use of IP addresses and names in the core network, the role of the E.164 numbers is taken over by IP addresses. However in case of voice services the identification of end-user access points will remain by the use of E.164 numbers. Migration to NGN doesn't require directly the change of the subscribers' phone number; however the NGN enables among others the implementation of national number portability for fixed telephone service. The opportunities can be realized by using uniform domestic number length and dialling method, practically closed numbering. The introduction of a 9-digit uniform, closed domestic numbering provides a consistent solution for the deficiencies of the present Hungarian numbering plan, too. Recently it can be reached in single step so that the present 9-digit domestic numbers and the short codes remain unchanged, the 8-digit domestic numbers are completed to 9-digit by the insertion of an appropriate digit, as well as the present and new numbering schemes can be in operation simultaneously.
Keywords: 330